2016
DOI: 10.1007/s12031-016-0845-1
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway

Abstract: NG2-expressing neural progenitors can produce neurons in the central nervous system, providing a potential cell resource of therapy for neurological disorders. However, the mechanism underlying neuronal differentiation of NG2 cells remains largely unknown. In this report, we found that a thrombospondin (TSP) family member, TSP4, is involved in the neuronal differentiation of NG2 cells. When TSP4 was overexpressed, NG2 cells underwent spontaneous neuronal differentiation, as demonstrated by the induction of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…High levels of TSP-4 have been detected in remodeling and failing hearts [3][4][5][6][7] , several cancers [8][9][10][11][12][13] , and atherosclerotic lesions 14 . Recently, new functions have been ascribed to TSP-4 in the cardiovascular system [5][6][7][14][15][16][17][18][19][20][21][22][23][24][25] , cancer [8][9][10][11][12][24][25][26][27][28][29] , skeletal muscle 30,31 , and nervous system [32][33][34][35][36] , but effects of TSP-4 on cellular responses and the regulation of TSP-4 expression remain poorly understood. For example, with an exception of TGFbeta 25 , stimuli inducing TSP-4 expression in tissues remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of TSP-4 have been detected in remodeling and failing hearts [3][4][5][6][7] , several cancers [8][9][10][11][12][13] , and atherosclerotic lesions 14 . Recently, new functions have been ascribed to TSP-4 in the cardiovascular system [5][6][7][14][15][16][17][18][19][20][21][22][23][24][25] , cancer [8][9][10][11][12][24][25][26][27][28][29] , skeletal muscle 30,31 , and nervous system [32][33][34][35][36] , but effects of TSP-4 on cellular responses and the regulation of TSP-4 expression remain poorly understood. For example, with an exception of TGFbeta 25 , stimuli inducing TSP-4 expression in tissues remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While TSP-4 is best known as a secreted extracellular matrix (ECM) protein, it became clear that some of its effects depend on its intracellular interactions: its binding to the ER lumenal domain of activating transcription factor 6α (Atf6α) protects cardiomyocytes from injury caused by ER stress responses 7 . Thus, this protein exerts its effect in multiple complementary ways: by initiating intracellular signaling and transiting through secretory pathways 38 , as well as by binding to its extracellular ligands and receptors upon secretion 5,6,14,24,30,33,37,[39][40][41][42][43][44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…High levels of TSP4 have been detected in remodeling and failing hearts [3][4][5][6][7], several cancers [8][9][10][11][12][13], and atherosclerotic lesions [14]. Recently, new functions have been ascribed to TSP4 in cardiovascular system [5][6][7][14][15][16][17][18][19][20][21][22][23][24][25], cancer [8][9][10][11][12][24][25][26][27][28][29], and nervous system [30][31][32][33][34], but effects of TSP4 on cellular responses and the regulation of TSP4 expression remain poorly understood. For example, with an exception of TGF-beta [25], stimuli inducing TSP4 expression in tissues remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although TSP4 ligands are not comprehensively investigated, recent work from our group and others identified several cell surface receptors that are used by TSP4 to exert its cellular effects. 14,17,27,28,33,34 We found that TSP4 regulates Mϕ migration and adhesion through α M and β 3 integrin subunits. 17 The migration of EC in presence of recombinant TSP4 relied on β 3 and α 2 integrin subunits (with α V β 3 not involved) and integrin α V β 5 , as well as on the GABA receptor α 2 δ-1, 14 a TSP4 receptor suggested by previous reports on the functions of TSP4 in nervous system.…”
Section: Introductionmentioning
confidence: 91%
“…1,2 Recent studies have demonstrated the importance of TSP4 in the cardiovascular system, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] cancer, 14,15,[18][19][20][21][22][23][24][25][26] and the nervous system. [27][28][29][30] Remarkably high levels of TSP4 have been found in failing and hypertrophied hearts, [11][12][13]16,31 atherosclerotic lesions, 17,31 and several cancers. 15,[18][19][20][21][22][23][24][25][26] These reports have placed considerable attention on this poorly studied TSP, but many of its functions and its regulation still remain unknown.…”
Section: Introductionmentioning
confidence: 99%